Brain-wide map of projections from mice ventral subiculum. (26th August 2016) - Tang, He; Wu, Gui-Sheng; Xie, Jing; He, Xiaobin; Deng, Ke; Wang, Huadong; Xu, Fuqiang; Luo, Huai-Rong
Highlights: Brain regions receive direct projections from ventral subiculum were identified. Brain regions receive secondary projections from ventral subiculum were determined. The transneuronal tracing of herpes simplex virus could be clearly identified. Abstract: The hippocampal formation plays a critical role in episodic memory formation and spatial navigation. Within the hippocampus, the subiculum is considered to be a hub connecting the hippocampal formation to the remainder of the brain. There are functional differences between the dorsal and ventral part of subiculum, while the ventral subiculum (vSub) plays a role in anxiety, stress and emotion. In the present study, we examined the projection of the ventral subiculum to the whole brain in mice by using a modified herpes simplex virus 1 strain H129 with an inserted fluorescent protein gene. In our experiments, the modified H129 transits the primary-order, second-order, and third-order neuronal projections at 36–44, 52–60 and 68–76 h after inoculation in mice, respectively. Our data revealed that vSub directly projects to the medial entorhinal cortex, amygdalohippocampal area, anterodorsal thalamic nucleus, medial hypothalamus, supramammillary nucleus, medial septal nucleus and adjacent diagonal band, the connections between median raphe nucleus and interpeduncular nucleus in brain stem, while ventral prefrontal cortex, laterodorsal tegmental nucleus and locus coeruleus receives second-order projections from vSub. Our data would help further understanding the functional connections of vSub with other brain regions.